2010
DOI: 10.1029/2009jd013784
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to special section on Climate and Weather of the Sun Earth System

Abstract: [1] In the special section on CAWSES (Climate and Weather of the Sun Earth System) a total of 19 papers are published covering several aspects of Sun-Earth coupling. Six papers concentrate on summer mesospheric ice clouds including detection by satellites, radarbased derivation of particle properties, and water vapor observations in the mesosphere. Solar radiation affects ice clouds on time scales of the 11 year solar cycle and 27 days. Stratospheric shrinking contributes significantly to long-term trends of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Being mainly excited in the troposphere by flow over terrain, by convection, or by spontaneous emission, GWs may propagate both vertically and horizontally over large distances to deposit their momentum and energy far away from their source upon instability or transience (e.g., Fritts and Alexander, 2003;Sato et al, 2009Sato et al, , 2012Preusse et al, 2009;Bölöni et al, 2016). Thus, GWs are an important mechanism that couples the middle and upper atmosphere to the troposphere (e.g., Lübken et al, 2010, and references therein). In addition, it has recently been shown that GWs also couple the middle atmosphere downward to the troposphere (Kidston et al, 2015, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Being mainly excited in the troposphere by flow over terrain, by convection, or by spontaneous emission, GWs may propagate both vertically and horizontally over large distances to deposit their momentum and energy far away from their source upon instability or transience (e.g., Fritts and Alexander, 2003;Sato et al, 2009Sato et al, , 2012Preusse et al, 2009;Bölöni et al, 2016). Thus, GWs are an important mechanism that couples the middle and upper atmosphere to the troposphere (e.g., Lübken et al, 2010, and references therein). In addition, it has recently been shown that GWs also couple the middle atmosphere downward to the troposphere (Kidston et al, 2015, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…We note that according to Skamarock (2004) only scales exceeding the grid spacing by several times are resolved. Model output is available every 6 h. Details about the model can be found in Malardel and Wedi (2016) and in references therein.…”
Section: Ecmwf Operational Analysis and Reanalysis Datamentioning
confidence: 99%
“…Thus, GW are a major means to couple the middle and upper atmosphere to the troposphere (e.g., Lübken et al, 2010, and references therein). In addition, it has recently been shown that GW also couple the middle atmosphere downward to the troposphere (Kidston et al, 2015, and references therein).…”
Section: Introductionmentioning
confidence: 99%